Luis Gordon Picardo. Un empresario en los primeros años del Opus Dei (1898–1932) / Luis Gordon Picardo. Businessman (1898-1932) - Pedro Pablo Ortuñez Goicolea; Luis Gordon Beguer (Studia et Documenta)
This article attempts to reconstruct the biography of one of the first members of Opus Dei. The intense normality and briefness of the protagonist’s life made many of the research phases difficult. However, the available information is enough to create a sketch of the character and personality of a faithful Christian, living in the trying political and economical situation of Spain during the first third of the twentieth century.